2004
DOI: 10.1002/eji.200425455
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Artemis following irradiation‐induced DNA damage

Abstract: Artemis is a DNA repair factor required for V(D)J recombination, repair of DNA damage induced by ionizing radiation (IR) or radiomimetic drugs, and the maintenance of genome integrity. During V(D)J recombination, Artemis participates in the resolution of hairpin-sealed coding ends, a step crucial to the constitution of the gene encoding for the antigen receptor of lymphocytes. The precise role of Artemis in the repair of IR-induced DNA damage remains to be elucidated. Here we show that Artemis is constitutivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
57
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 32 publications
8
57
0
Order By: Relevance
“…In contrast, we have found that mice with combined deficiency for Artemis and ATM are viable, with some living up to at least 9 months. In this regard, recent studies suggest that Artemis may, in fact, be epistatic to ATM in the IR-induced ATM signaling pathway (47,57,58). The viability of Artemis͞ATM double-deficient mice suggests that synergistic function of DNA-PKcs with ATM in preventing embryonic lethality does not involve Artemis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we have found that mice with combined deficiency for Artemis and ATM are viable, with some living up to at least 9 months. In this regard, recent studies suggest that Artemis may, in fact, be epistatic to ATM in the IR-induced ATM signaling pathway (47,57,58). The viability of Artemis͞ATM double-deficient mice suggests that synergistic function of DNA-PKcs with ATM in preventing embryonic lethality does not involve Artemis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Artemis is an ATM phosphorylation target [12,[22][23][24]. The model proposed is that ATM is required for Artemis-dependent end-processing and hence Artemis-dependent DSB repair [12].…”
Section: Apoptosismentioning
confidence: 99%
“…DNA-PKcs-dependent phosphorylation sites in the C-terminal portion of the Artemis have been suggested to have an important regulatory role in the activity of the protein (31), most of them not being SQ or TQ consensus DNA-PKcs sites (31). In addition, an ATM-and ATR-dependent phosphorylation of Artemis has been reported in cells (34,36,37,38), but its relation to Artemis function in DSB repair is not yet fully understood. Moreover, Artemis could have another role in the regulation of cell cycle progression following DNA damage, including UV irradiation (35,38), although this cell cycle function was not confirmed by others (39).…”
mentioning
confidence: 99%